A survey on opinions, perceptions and attitudes of Swedish veterinarians—the Swedish veterinary disciplinary board - Egenvall, Agneta; Enlund, Karolina Brunius; Holmquist, Terese; Rosenquist, Magnus (Frontiers in Veterinary Science, 2026)
IntroductionVeterinary disciplinary boards (VDBs) evaluate complaints from animal owners regarding the healthcare of animals. It is important that these boards safeguard the quality of veterinary care, but how veterinarians are affected psychosocially is also relevant. The aim of this study was to explore perceptions, attitudes and experiences among veterinarians concerning the Swedish VDB, taking account of respondent characteristics.Materials and methodsA web-based questionnaire targeting veterinarians in current or former clinical practice was launched in 2024. There were 1,054 responses initiated and of these 819 were completed.ResultsHalf of the respondents had had complaints filed against them, but only 1 in 10 had received a sanction. Few veterinarians left clinical work because of VDB-related issues. Many veterinarians were relatively unaware about VDB processes and did not worry excessively about complaints being filed, respondents replying ‘cannot evaluate’ ranged 33–61% for these questions. However, 18% worried very much about having complaints filed. While veterinarians identified that VDB assessments increased record keeping and emphasis on communication, they generally felt that the VDB had relatively little effect on the patient outcomes for animals seen. Some animal owners who had previously submitted complaints would be denied access if veterinarians were aware of those complaints. Instituting operational oversight was considered a valuable adjunct to current regulation (43.7% ‘agreed completely’).DiscussionOverall, respondents found that the VDB performs an important task, while areas for improvement were identified, including transparency of procedures. One way to mitigate worries of complaints could be increased education and training in soft skills, including skills for communication and management of complaints.